PANDANGAN HUKUM ISLAM TENTANG ADAT HITUNGAN DALAM PERKAWINAN DI KECAMATAN CIBADAK KABUPATEN SUKABUMI: Islamic Legal Perspective on the Dowry Calculation Custom in Marriage in Cibadak District, Sukabumi Regency - Malik, Ikbar Maulana (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2017)
AbstractThere is a custom in Cibadak Sub-District, Sukabumi Regency, that a prospective spouse candidate and the wedding date are determined through a particular date calculation. The community members believe this calculation will give them a good day to carry out the ceremony and the newly wed will have harmonious marriage. This study aimed to describe the custom practice through the perpective of Islamic law. The applied method of this study is descriptive analysis upon with qualitative data, collected through desk study, interviews, and observation. This study shows that most of marriage conducted in the district applied the calculation, since they believe this custom will bring happiness to the couple. This intention is correspond to the aims of marriage based on the the Republic of Indonesia Compilation of Islamic Law 1991 which are to realize a sakinah, mawaddah and warahmah domestic life.This custom is permissible since it is merely part of effort to achieve the marriage goals.Keywords: Marriage, customary law, Islamic lawAbstrakMasyarakat Kelurahan Cibadak Kecamatan Cibadak Kabupaten Sukabumi, memiliki kebiasaan untuk melakukan hitungan tanggal dalam menentukan pasangan dan hari baik untuk menikah. Hal itu dipercaya akan mencapai tujuan dalam perkawinan yakni keharmonisan dalam keluarga. Tulisan ini bertujuan untuk memaparkan kebiasaan tersebut dihubungkan dengan perspektif hukum Islam. Penelitian ini menggunakan metode deskriptif analitis dengan jenis data kualitatif. Hasil penelitian menunjukkan bahwa sebagian besar perkawinan yang dilakukan di kelurahan ini menggunakan adat hitungan sebelum akad perkawinan. Hal tersebut dilakukan karena masyarakat setempat percaya bahwa ia akan mendatangkan kebaikan dalam kehidupan rumah tangga yang akan mereka lalui. Kepercayaan tersebut searah dengan tujuan perkawinan yang diangkat antara lain dalam Kompilasi Hukum Islam yaitu untuk mewujudkan kehidupan rumah tangga yang sakinah, mawaddah dan warahmahâ€. Kebiasaan tersebut dapat diterima mengingat ia hanya sekedar wasilah atau ikhtiar semata. Â Kata Kunci:Perkawinan, hukum adat, Hukum Islam